Silent Victims of COVID-19 - Elham Navab; Fatemeh Bahramnezhad (Iran University of Medical Sciences, 2019)
This letter intends to explain what the authors have experienced in Iran from the beginning of COVID-19 spread about the process of care and treatment of the patients with other diseases.